1999
DOI: 10.1046/j.1365-3059.1999.00345.x
|View full text |Cite
|
Sign up to set email alerts
|

Parasitism of macroconidia, chlamydospores and hyphae of Fusarium culmorum by mycoparasitic Pythium species

Abstract: Parasitism of macroconidia and endoconidial chlamydospores of Fusarium culmorum by Pythium oligandrum was studied on water agar (WA), corn-meal agar (CMA) and glass slides. Loss of cytoplasmic content in F. culmorum spores was followed by complete degradation, and P. oligandrum produced an abundance of oogonia on the parasitized macroconidia. A simple method for assessing the relative aggressiveness of isolates is presented, based on the percentage of macroconidial cells devoid of cytoplasm. Parasitism of macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…In different studies, the antagonist Clonostachys rosea reduced and suppressed conidia of Botrytis cinerea (Sutton et al, 1997;Morandi et al, 2003). This behaviour was also observed when mycoparasitic Pythium oligandrum was confronted against Fusarium culmorum in dual culture (Davanlou et al, 1999). Studies of dual cultures of T. harzianum and other species revealed inhibition of germination but no suppression of conidia (Lorito et al, 1993a(Lorito et al, , 1993bZimand et al, 1996;Kapat et al, 1998;Golam Mortuza and Ilag, 1999).…”
Section: Mycelial Interactions Between Trichoderma Harzianum and Nigrmentioning
confidence: 92%
See 1 more Smart Citation
“…In different studies, the antagonist Clonostachys rosea reduced and suppressed conidia of Botrytis cinerea (Sutton et al, 1997;Morandi et al, 2003). This behaviour was also observed when mycoparasitic Pythium oligandrum was confronted against Fusarium culmorum in dual culture (Davanlou et al, 1999). Studies of dual cultures of T. harzianum and other species revealed inhibition of germination but no suppression of conidia (Lorito et al, 1993a(Lorito et al, , 1993bZimand et al, 1996;Kapat et al, 1998;Golam Mortuza and Ilag, 1999).…”
Section: Mycelial Interactions Between Trichoderma Harzianum and Nigrmentioning
confidence: 92%
“…Previously the authors investigated other interactions and all studies confirmed this technique. There are few researches and the usual techniques to study fungal relations are tedious SEM preparations or light microscopical observations (Madi et al, 1997;Davanlou et al, 1999;Moussa, 2002;Zadworny et al, 2004).…”
Section: Mycelial Interactions Between Trichoderma Harzianum and Nigrmentioning
confidence: 99%
“…Trichoderma harzianum is an effective biocontrol agent which mycoparasitized on Sclerotium rolfsii, Rhizoctonia solani and Pythium aphanidermatum (Elad et al 1980(Elad et al , 1983Sivan et al 1984;Benhamou and Chet 1996;Chet 1987Chet , 1990. The process involved in mycoparasitism may consist of sensing the host, followed by directed growth, contact, recognition, attachment, penetration, and exit (Chet et al 1981;Benhamou et al 1999;Davanlou et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Also, Phytium species are mycoparasites of this pathogen fungus, and attach to its hyphae, macroconidia and chlamidosphores (Foley and Deacon 1985;Hockenhull 1996, Laing andDeacon 1991). Davanlou et al (1999) showed that the initial contact between P. oligandrum and macroconidia of F. culmorum was followed by coagulation, lost of cytoplasmatic content and degradation of its cell wall.…”
Section: Micromorphological Studies Of Antagonistic Activitymentioning
confidence: 99%